Analysis of the Role of the Latvian Natural Gas Network for the use of Future Energy Systems: Hydrogen from Res - Kleperis, Janis; Boss, Dainis; Mezulis, Ansis; Zemite, L.; Lesnicenoks, Peteris; Knoks, Ainars; Dimanta, I. (De Gruyter, 2021)
As EU is steadily moving in the direction of emission reduction, each country must develop plans to decarbonise the transport and energy sectors. In Latvia, transport sector is one of the biggest emission sources. The heating applications come next. Both require carbon containing fuels and a transfer to carbon neutral fuel is necessary; therefore, hydrogen may be the answer to achieve the overall EU targets. As Latvia has renewable energy sources, some production, storage and use of hydrogen are possible. Currently clear guidelines for Latvia have been investigated. The existing natural gas network may be used for two tasks: large-scale hydrogen transportation and decarbonisation of natural gas network. To open the natural gas networks for hydrogen, the first evaluations are made and a possible scenario for hydrogen implementation in network supplying consumers in the household sector is analysed to evaluate decarbonisation with an overarching goal of carbon neutrality. ---//---This work is licensed under a CC BY 4.0 license.
The research has been funded by the Ministry of Economics of the Republic of Latvia, project “Trends, Challenges and Solutions of Latvian Gas Infrastructure Development (LAGAS)”, project No. VPP EM-INFRA-2018/1-0003.
Keywords: Research Subject Categories::NATURAL SCIENCES:Physics; Decarbonisation; HCNG blending; hydrogen; natural gas; NG networks